Sliding mode current control of a single-phase three-level active rectifier - Monteiro, Vítor Duarte Fernandes (2022)
This paper presents the sliding mode current control (SMCC) applied to control the power grid current of a single-phase three-level active rectifier (STAR). When contrasted with typical topologies of power factor correction, the STAR converter works with three voltage levels, giving a set of benefits. By pondering the possible wide range of applications of the STAR converter, the proposed control based on the SMCC suggests a robust current tracking. With the intention of managing the power grid current, throughout every sampling period, the SMCC specifies the reference for the modulation and the state of all switching devices, intending to diminish the current error. A whole clarification involving the SMCC functioning is displayed along the paper, which is founded fitting the whole operation of the STAR converter. The taken computational results, contemplating crucial working conditions of power ranges and rapid variations, justify the correct application of the SMCC when employed to control the power grid current of the STAR converter. An assessment of the SMCC is also given in contrast with a different current control, letting to verify the exact application and advantages of the SMCC.